Akuntabilitas dan Pengelolaan Keuangan di Masjid: (Studi Kasus Masjid Al-Iqro’ Kota Pematangsiantar) - Sumaizar Sumaizar; Eko Deswin Miechaels Siringo-ringo; R. Elfrida Panjaitan; Septiany A Siallagan (Owner : Riset dan Jurnal Akuntansi, 2019)
This research was conducted at Al-Iqra’ Mosque, Pematangsiantar. This  study aims to find out hoe accounting and practice financial management carried out by the mosque management.This research was conducted using qualitative methods, collection of data conducted with interviews and information retrieval from the mosque cash report Al-Iqra’. The data source was obtained from the statement of chairmen, treasurer and jama’ah Al-Iqra’ Mosque who knows about practice accounting and financial management at the Al-Iqra’ Mosque. Based on results of data conducted by researchers, shows that the management the mosque has adopted accounting practices,although it still uses methods simple  one. Financial management is recorded well, although still simple, but the method lasts well for years.